Evaluation of stability and in vitro wound healing potential of melatonin loaded (lipid enriched) chitosan based microspheres - Romić Marieta Duvnjak; Sušac Anja; Lovrić Jasmina; Cetina-Čižmek Biserka; Filipović-Grčić Jelena; Hafner Anita (Acta Pharmaceutica)
The aim of this study was to evaluate long-term stability and assess the wound healing potential of the innovative melatonin-loaded lipid-enriched hybrid system compared to conventional melatonin-loaded chitosan microspheres. The hybrid system contained nanostructured lipid carrier incorporated in the chitosan matrix, in order to modify melatonin release and alter physicochemical characteristics of the delivery system. Stability testing was performed during a six-month period under two conditions: refrigerated (5 ± 3 °C) and at room temperature (25 ± 2 °C/60 ± 5 % RH). Samples stored at both conditions were analyzed in terms of particle size, zeta potential, moisture content and thermal properties. At the end of testing, drug content was determined in all samples. Dressings wound healing potential was assessed by in vitro scratch test using human skin fibroblast cell line. Although both systems showed good stability characteristics, the addition of lipids in the system has improved its wound healing potential.